HUBUNGAN KECEMASAN SOSIAL DENGAN PENGUNGKAPAN DIRI DIMODERATORI DUKUNGAN SOSIAL ONLINE PADA INDIVIDU PENGGUNA MEDIA SOSIAL - Dinar, Lativa; Fakhri, Nur Fitriany; Ridfah, Ahmad (Institut Agama Islam Negeri (IAIN) Manado, 2023)
ABSTRACTIndividuals experience various events when disclosing themselves in the real world which trigger social anxiety so that social support is needed so that individuals can disclose themselves both in the world and on social media. The purpose of this study was to determine whether there is a relationship between social anxiety and self-disclosure moderated by online social support for individuals who use social media. The subjects in this study were 310 individual social media users in South Sulawesi obtained using the accidental sampling technique. Self-disclosure was measured using the Revised Self Disclosure Scale, social anxiety was measured using the Social Anxiety Scale for Adolescents and online social support was measured using Online Social Support. The data analysis used in this study is the process test from Hayes. The results showed that there was a significant relationship between social anxiety and self-disclosure moderated by online social support for individual social media users. Online social support strengthens the relationship between social anxiety and self-disclosure in individual social media users.Keywords: online social support, self disclosure, social anxiety, social mediaABSTRAKIndividu mengalami berbagai peristiwa saat melakukan pengungkapan diri di dunia nyata yang memicu kecemasan sosial sehingga dibutuhkan dukungan sosial agar individu dapat melakukan pengungkapan diri baik di dunia maupun di media sosial. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat hubungan kecemasan sosial dengan pengungkapan diri dimoderatori dukungan sosial online pada individu pengguna media sosial. Subjek dalam penelitian ini adalah 310 individu pengguna media sosial di Sulawesi Selatan didapatkan menggunakan teknik accidental sampling. Pengungkapan diri diukur menggunakan Revised Self Disclosure Scale, kecemasan sosial diukur menggunakan Social Anxiety Scale for Adolescents dan dukungan sosial online diukur menggunakan Online Social Support. Analisis data yang digunakan dalam penelitian ini adalah uji process dari Hayes. Hasil penelitian menunjukkan ada hubungan yang signifikan antara kecemasan sosial terhadap pengungkapan diri dimoderatori dukungan sosial online pada individu pengguna media sosial. Dukungan sosial online menguatkan hubungan antara kecemasan sosial terhadap pengungkapan diri pada individu pengguna media sosial.Kata Kunci: Dukungan sosial online, kecemasan sosial, media sosial, pengungkapan diri